2009
DOI: 10.3141/2135-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Neighborhood Trail Development on Active Travel Behavior and Overall Physical Activity of Suburban Residents

Abstract: Many studies have examined the impact that the built environment has on physical activity. Much existing research posits that if communities will provide and improve active infrastructure such as trails, sidewalks, and bike lanes, people will become more physically active. However, most of these studies have used cross-sectional methods that have allowed them to establish correlations but not behavioral causality. In this pilot project, a longitudinal design is used to assess a trail construction impact on act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Though as a result of the trail a loop of 2.5 miles was created, adequate signposting was missing, which possibly limited the trail's effectiveness. In line with this the authors mentioned that a lack of information could have influenced the negative effects (Burbridge and Goulias, 2009). The extension of the UK National Cycle Network (Jones, 2012) was also implemented without any additional tools and could therefore have resulted in no effect on a mode shift.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Though as a result of the trail a loop of 2.5 miles was created, adequate signposting was missing, which possibly limited the trail's effectiveness. In line with this the authors mentioned that a lack of information could have influenced the negative effects (Burbridge and Goulias, 2009). The extension of the UK National Cycle Network (Jones, 2012) was also implemented without any additional tools and could therefore have resulted in no effect on a mode shift.…”
Section: Discussionmentioning
confidence: 89%
“…Another architectural and urbanistic adjustment stimulating a mode shift is the building of a neighbourhood trail (physical tool) in West Valley City in Utah (Burbridge and Goulias, 2009). The aim of the neighbourhood trail was to provide the public with a facility for transportation as well as recreation.…”
Section: Architectural and Urbanistic Adjustmentsmentioning
confidence: 99%
“…Many studies have relied on the Theory of Planned Behaviour (TPB, Ajzen, 1991), a model grounded in social psychology, to explain the behavioural intention of bicycle usage (Bamberg & Schmidt, 1994;Burbidge & Goulias, 2010;De Bruijn, Kremers, Singh, van den Putte, & van Mechelen, 2009;Eriksson & Forward, 2011;Heinen, Maat, & van Wee, 2011;Muñoz, Monzon, & Lois, 2013). The aim of this study was to enrich the TPB by including social identity as a predictor variable, because behaviour is not determined by purely utilitarian considerations, but also by the symbolic consequences for one's self-concept and identity as a member of certain groups (Mannetti, Pierro, & Livi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…28 Furthermore, two U.S. studies revealed no effects of proximity to new paths, with one study finding only 2 bicycle trips per 386 travel diary days 29 and the other finding only 2 of 366 residents making any bicycle trips pre-trail construction and a decrease in cycling time post-trail construction. 30 Even after screening for bike ownership, a recent Portland study showed no increase in biking among nearby bike owners near a new greenway.…”
Section: Introductionmentioning
confidence: 99%